Produção de podofilotoxina em culturas de raízes in vitro de Hyptis suaveolens: abordagens fitotécnicas e analíticas - Sabato, Sâmia Torres Silva (2020)
Podophyllotoxin (PTOX), a lignan with anticancer action, among other properties, may be present in the root of H.suaveolens. This study aimed to validate an analytical method to quantify PTOX on the roots of the species and optimize its in vitro production. The concentrations of growth regulators (AIB, ANA, 2,4-D), the composition of the basic culture medium (concentration of vitamins and myo-inositol), the quality of light, and natural ventilation were modified in this type of cultivation. The analytical validation presented the following results: selectivity (purity: 99%), suitability of the system (Rs = 2.92; N = 7064; K = 1.23; T = 1.31; DPR = 0.61% ), intraday precision (dpr = 2.43%), intermediary precision (dpr = 2.96%), linearity (y = 14.258,498x + 3019.954; R² = 0.997), accuracy (3-level recovery percentage: 90.47%, 98.03%, and 101.85%.), robustness (the method is not robust regarding the volume of chloroform recovered in the extraction and is robust regarding small changes in the chromatographic analysis method), and quantification (5.25 ng) and detection (0.5 ng) limits. Regarding in vitro root cultivation in liquid MS medium, the combination of 1 mg L-1 of IBA + 0.5 mg L-1 of ANA presented the highest value for root dry matter (248.76 mg) and PTOX, 179.97 μg g-1 of root and 0.73 μg ml-1 of culture medium. In the second experiment, the cultivation of roots in liquid MS medium, with half the standard amount of vitamins and myo-inositol from MS, showed good root dry matter (198.88 mg) and PTOX (6.01 μg g-1 of root). PTOX was not found in the culture medium in this essay. In the third experiment, adventitious roots formed on the leaves of H. suaveolens only in the absence of light and under red LED light. The root dry matter obtained in these treatments was statistically equal, 21.84 and 29.81mg, respectively. In the absence of light, there was a greater production of PTOX (10.72 μg g-1 of root). In the fourth experiment, light quality and natural ventilation, the treatment with no light and without membranes allowed greater root dry matter (84.02 mg) and PTOX (46,68 μg g-1). In the fifth experiment, regarding the induction of leaf roots in a semi-solid MS medium, 2.0 mg L-1 of ANA enabled the formation of greater root dry matter (45.53 mg). The treatment 1 mg L-1 of IBA enabled the highest production of PTOX (9.96 μg g-1 root). Regarding the induction of roots in nodal segments, the treatment with 0.5 mg L-1 of IBA enabled greater dry matter of adventitious roots (37.62 mg). PTOX was higher under treatments 1 and 2 mg L-1 of ANA (9.97 and 9.95 μg g-1 root). The cultivation of H.suaveolens roots in liquid MS medium with 1 mg L-1 of IBA + 0.5 mg L-1 of ANA in the absence of light was the most efficient among the analyzed systems to obtain PTOX.